GE_GERICHTE C/18853/2017 vom 12. Juli 2018 - GE Cour de justice (2018)
BAIL À LOYER ; TACITE ; RÉSILIATION ; BAILLEUR(BAIL À LOYER) ; DROIT À LA PREUVE ; DROIT D'ÊTRE ENTENDU ; NOTORIÉTÉ | CPC.150.al1; CPC.151; Cst.29.al2; CO.1.al2